ANALYSIS OF THE INFLUENCE OF OWNERSHIP STRUCTURE ON THE LEVEL OF TAX AVOIDANCE IN PROPERTY AND REAL ESTATE SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE (IDX) FOR THE PERIOD 2021–2023 - Putri, Trianita Kusuma; Awalina, Putri; Sahara, Khasanah (Penelitian dan Pengembangan Ilmu, 2025)
This study aims to analyze the effect of ownership structure on the level of tax avoidance in property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2021–2023. The research method used is quantitative with a multiple linear regression approach. The sample was selected using the purposive sampling method and resulted in 14 companies as samples, with a total of 42 annual financial report data. The results of the study indicate that ownership structure partially or simultaneously affects the level of tax avoidance. The implications of this study are important for investors in considering ownership structure when making investment decisions, as well as for regulators to understand the role of ownership in tax compliance. This study suggests that companies increase transparency and good governance in ownership structures. In addition, the Directorate General of Taxes and the Financial Services Authority (OJK) are expected to strengthen supervision and reform tax policies to prevent tax avoidance practices.